Presentation: Decentralization, Social Policies and Participation - Allpanchis, Revista (2004)
Peru began a decentralist reform at the end of 2002. The previous attempt (1989-1992) culminated, unnoticed, with the self-coup promoted by Alberto Fujimori backed by citizen indifference to the future of the regional governments of that time.